Readibility Level of Reading Texts in the English Textbook Entitled English Alive for Senior High School Grade X Published by Yudhistira - Rohmatillah, Rohmatillah (English Education: Jurnal Tadris Bahasa Inggris, 2015)
The objectives of this research are to find out kinds of text contained in the reading passage found in English textbook entitled English Alive for Senior High School Grade X published by Yudhistira and  the readibility level of reading text material in English textbook entitled English Alive for Senior High School Grade X published by Yudhistira.This study is a descriptive qualitative study which used content analysis as the method of the study. The method is used to describe the content of the textbook. One of the purposes of this method is to identify bias, prejudice, or propaganda in textbook presentation. The object of this study is English textbook entitled English Alive for Senior High School Grade X first and second semester published by Yudisthira. The textbook consists of ten Chapters with illustrations. The book composed based on KTSP curriculum. The data were collected by using document analysis. In calculating readibility level, the researcher employed the Flesch readability formula.Research findings reveals that from the result of analysis there are five kinds of text, namely recount, narrative, procedure, descriptive and news items texts. Based on the result of calculating the readibility level only five texts from sixteen texts are relevant to the students of Senior High School.